How much do academic performance, lifestyle, and social relationships explain depressive symptoms in Filipino university students? A regression model - Baring, Rito V. (Animo Repository, 2020)
Further systematic data on the predictors of depressive symptomatology are crucial due to the need to address the worsening mental health problems among young people in the Philippines. A regression model with seven predictors on academic performance, lifestyle, and social relationships was developed and tested. Data were drawn from a survey sample of 3,049 Filipino university students from Metro Manila, the Philippines. The predictors examined for their relationships with depressive symptoms as the dependent variable included cumulative grade-point average, number of hours spent on vigorous physical activity, number of hours spent using Facebook, number of bottles/glasses of alcohol taken, number of religious activities, and level of relational closeness with parents and peers. The predictors were each found to be statistically significantly related to depressive symptoms; relational closeness with parents and with peers were the strongest predictors. The model was statistically and significantly robust, albeit with modest predictive quality (R=0.320) as well as modest predictive strength (R2=0.103). As the model is formative, there is a need to continually examine, even elevate, its predictive power. In its current state, the model would be useful for triggering discourse, research, and intervention towards the prevention and control of this mental health problem and its pernicious effects on young people. © 2020 by De La Salle University.